Letter - Stolz, George
028-0178-001 INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE: President: W. M Citrine, Great Britain. Vice-President: H. Jacobsen, Denmark; L. Jouhaux, France; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary: W. Schevenels. TELEGRAMS: INTERFED-PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA Letter: F. I. de Sol No. 170 30th September 1936. Mr. Walter M. Citrine, LONDON. Dear Comrade Citrine, In reply to your letter of the 25th September, we are enclosing herewith our formal receipt for your further grant of £5,000 to the Spanish fund, for which we are extremely grateful. Yours sincerely, G. Stolz, Assistant Secretary: 292/946/28/178